Derive the equation for **the volume of an n-dimensional sphere**

\[\displaystyle \text{the volume of an n-dimensional sphere } = \frac{\sqrt{{\pi}^{n}}}{\Gamma\left(\frac{n}{2} + 1\right)} {R}^{n}\]

\(R\) is the radius of the sphere.

This one is something special because I myself am not able to prove it until now.

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestLet \(V_{n}\) be the volume of the \(n\) dimension sphere. Note that,\(V_{n} \propto R^n\) where \(R\) is the radius of the sphere.

\(\implies V_{n} = k_{n} R^n\)

From the definition of an \(n+1\) dimension sphere,

\(\displaystyle {x_{1}}^2 + {x_{2}}^2 + \ldots + {x_{n+1}}^2 = R^2\)

\(\displaystyle \implies {x_{1}}^2 + {x_{2}}^2 + \ldots + {x_{n}}^2 = R^2 - {x_{n+1}}^2\)

Divide the \(n+1\) sphere into small "pieces" of \(n\) sphere, each of length \(d x_{n+1}\) with radius as \(R_{*} = \sqrt{R^2 - {x_{n+1}}^2}\)

\(\displaystyle \implies V_{n+1} = 2 \int_{0}^{R} k_{n} \left(\sqrt{R^2 - {x_{n+1}}^2}\right)^n d x_{n+1}\)

\(\displaystyle \implies k_{n+1} R^{n+1} = 2 \int_{0}^{R} k_{n} \left(\sqrt{R^2 - y^2}\right)^n d y\)

\(\displaystyle \implies k_{n+1} R^{n+1} = 2 R^n \int_{0}^{R} k_{n} \left(1 - \dfrac{y^2}{R^2} \right)^{\dfrac{n}{2}} d y\)

Putting \(\displaystyle t = \left(1 - \frac{y^2}{R^2} \right)\), we have,

\(\displaystyle k_{n+1} = k_{n} \int_{0}^{1} t^{\frac{n}{2}} (1-t)^\frac{-1}{2}\)

\(\displaystyle \implies \dfrac{k_{n+1}}{k_{n}} = \operatorname{B} \left(\frac{n}{2} + 1 , \frac{1}{2} \right)\)

\(\displaystyle \implies \dfrac{k_{n+1}}{k_{n}} = \dfrac{\Gamma \left( \frac{n}{2} +1 \right) \Gamma \left(\frac{1}{2}\right)}{\Gamma \left(\frac{n}{2} + \frac{3}{2} \right)}\)

\(\displaystyle \implies \prod_{n=1}^{m} \dfrac{k_{n+1}}{k_{n}} = \prod_{n=1}^{m} \dfrac{\Gamma \left( \frac{n}{2} +1 \right) \Gamma \left(\frac{1}{2}\right)}{\Gamma \left(\frac{n}{2} + \frac{3}{2} \right)} \ (*)\)

Clearly, \((*)\) telescopes, thus,

\[V_{m} = \dfrac{\sqrt{{\pi}^m}}{\Gamma\left(m + \dfrac{1}{2}\right)} R^m\]

Log in to reply

Comment deleted Dec 05, 2015

Log in to reply

Brilliant! I have seen other proofs of the same which done using Gaussian integral but i must tell you how much I admired your solution.

I'm sorry I didn't see it before. It had been a week? How I missed it?

But I must tell you that you should also see other approaches available on the net using multiple integrals. That's because there are many questions relating to this one which is easiest to get done by that approach.

Log in to reply